Demographic Transition and Education in Kerala - K S James (Economic and Political Weekly December 23,1995, 1995)
Between 1990 and 1993 the Kerala government closed down several 'uneconomic' schools, where the student strength had gone down abysmally. This sparked off a controversy at the academic and political levels and has focused attention on the impact of the demographic transition on the education sector.